2021
DOI: 10.1523/eneuro.0507-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cerebellar Neural Circuits in Active Avoidance Conditioning in Zebrafish

Abstract: When animals repeatedly receive a combination of neutral conditional stimulus (CS) and aversive unconditional stimulus (US), they learn the relationship between CS and US, and show conditioned fear responses after CS. They show passive responses such as freezing or panic movements (classical or Pavlovian fear conditioning), or active behavioral responses to avoid aversive stimuli (active avoidance). Previous studies suggested the roles of the cerebellum in classical fear conditioning but it remains elusive whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, this observation is in accordance with other zebrafish models in which PCs are impaired. Rather than gross defects in locomotor control, socio-emotional functions such as conditioned active avoidance are observed [35]. Interestingly, in the established zebrafish SCA1 model, PC degeneration did not appear to progress equally in all regions of the corpus cerebelli.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, this observation is in accordance with other zebrafish models in which PCs are impaired. Rather than gross defects in locomotor control, socio-emotional functions such as conditioned active avoidance are observed [35]. Interestingly, in the established zebrafish SCA1 model, PC degeneration did not appear to progress equally in all regions of the corpus cerebelli.…”
Section: Discussionmentioning
confidence: 97%
“…A fast recovery of mature and stable physiological patterns in regenerating PCs predicts a similarly quick recovery of PC function in governing behavior. In zebrafish larvae, impaired PC function has been shown to result in eye movement defects by means of saccade performance during the optokinetic response (Matsui et al, 2014; Kazuhiko Namikawa et al, 2019), to lead to decreased exploratory behavior in anxiety-related tests and to cause delayed recovery from conditioned fear response (Elsaey et al, 2021; Koyama et al, 2021; Matsuda et al, 2017; Kazuhiko Namikawa et al, 2019). Indeed, we observed such behavioral deficits during acute PC apoptosis at 2dpt, but also the functional recovery for visuomotor behavior (optokinetic response), locomotor activity (hyperactivity) and socio-emotional behavior (thigmotaxis), between 9-11 days post-ablation, when the PC layer is only partially replenished (below 50% PC regeneration).…”
Section: Discussionmentioning
confidence: 99%
“…The zebrafish and mammalian cerebellum share nearly all neuronal cell types with their circuitry, physiology and function being conserved (Hashimoto and Hibi, 2012;Hibi et al, 2017;Koyama et al, 2021;Matsuda et al, 2017;Volkmann et al, 2010). Furthermore, clarification of the developmental origin and differentiation program of zebrafish cerebellar neurons, their physiology and functional contribution to locomotor control, motor learning and socio-emotional behavior has been revealed, and these studies have laid a solid foundation for regeneration surveys of cerebellar neurons (Chang et al, 2021b(Chang et al, , 2020Harmon et al, 2017;Kidwell et al, 2018;Knogler et al, 2019Knogler et al, , 2017Koyama et al, 2021;Markov et al, 2021;Matsuda et al, 2017;Matsui et al, 2014;Rieger et al, 2009;Volkmann et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the understanding of cellular processes supporting cerebellar contributions to fear memory formation has been improved by subsequent recent studies in a range of species. For example, in zebrafish, Takeuchi et al (2017) and Koyama et al (2021) have highlighted a key role of cerebellar granule cells in recovery from fear responses whilst Dubois and Liu (2021) revealed a strict requirement for decreasing inhibitory transmission in the cerebellar cortex molecular layer in order to reset cerebellar circuits for fear extinction learning in mice. Whilst Sacchetti et al (2004) mice deficient in parallel fibre-Purkinje cell synaptic potentiation had impaired fear response to conditioned stimuli (Sacchetti et al, 2004), Han et al (2021) further revealed that signal transducer and activator of transcription 3 (STAT3)-dependent molecular regulation of glutamatergic input to Purkinje cells is indispensable for proper expression of fear memory.…”
Section: Intra Cerebellar Micro-circuit Mechanisms Supporting a Role ...mentioning
confidence: 99%